(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the Efforts to Improve Learning Outcomes of Basic Side Kick Pencak Silat Movements Using Modified Rubber Tire Tools for Class VII.1 Students at SMP Negeri 3 Palembang. The method in this experimental research is a pre-experimental design, and the research design is a one-group pretest-posttest design. There is also the population of this study, namely all students, and a total sampling technique of 26 students. The technique in collect this data uses the pencak silat crescent kick test, and there is also the analysis technique used in this study is the t-test. Based on the results of the t-test analysis, the t-count value = 12.31 is more than the t-table (0.05) (dk = n-1) = 2.120, so that H0 is rejected. Likewise with the sig. Value for 0.000 <0.025. Based on the results of the research that has been conducted, it was found that the approach of using rubber tire tool modification is very effective in improving the learning outcomes of physical education in class VII.1 of SMPN 35 Palembang. In the process of learning Physical Education, Sports and Health, there needs to be an interesting learning innovation so that students are interested in learning Physical Education, Sports and Health.